Feeder-cell-free system for ex vivo production of natural killer cells from cord blood hematopoietic stem and progenitor cells - Martin Corredera, Marta; Paillet, Juliette; Gaudeaux, Pierre; Blein, Tifanie; Sadek, Hanem; Rault, Pauline; Berriche, Asma; Roche-Naude, Jeanne; Lagresle-Peyrou, Chantal; Soheili, Tayebeh-Shabi; André, Isabelle; Moirangthem, Ranjita Devi; et al. (Frontiers in Immunology, 2025)
IntroductionNatural Killer (NK) cells hold significant promise as therapeutic agents in immuno-oncology due to their ability to target and eliminate cancerous and infected cells without causing graft-versus-host disease or cytokine release syndrome. However, the limited availability of robust, scalable methods for generating clinical-grade NK cells remains a limiting factor to broader clinical application.MethodsHere we report the development of a novel feeder-cell-free culture system optimized for producing NK cells from cord blood-derived CD34+ hematopoietic stem and progenitor cells (HSPCs). Our method eliminates the need for feeder cells while achieving high yields of NK cells that exhibit unique marker expression and cytotoxic functions. Cord blood CD34+ HSPCs were cultured in our established hDLL 4 culture system and generated large numbers of human T lymphoid progenitors (ProTcells) in 7 days. ProTcells were further cultured in a hDLL4-free, feeder-cell-free system for NK cell differentiation and supplemented with cytokines. Following a 7- or 14-day culture, this method produced highly pure NK cell populations (>90% CD3–CD56+).ResultsFlow and mass cytometric analysis confirmed the expression of activating receptors, transcription factors (ID2, T-bet) and cytotoxic molecules (perforin, granzyme A/B), all essential for ProT-NK cell functionality. These cells are in an immature state, indicated by the absence of maturation markers (CD16, KIRs). Functional assays demonstrated that these ProT-NK cells are capable of degranulation and cytokines production (TNFα) upon stimulation with K562 target cells and showed cytotoxicity against K562 cells superior to that of Peripheral Blood (PB)-NK. In NSG-Tg(hIL-15) mice, ProT-NK cells colonize bone marrow, the liver, and the spleen and persist and mature in bone marrow for at least 9 days post-injection. Compared to ProT-NK D21, ProT-NK D14 was superior in functional and homing potential. In vivo, an anti-tumor assay that uses a subcutaneous K562 model has demonstrated the anti-tumor potential of ProT-NK cells.DiscussionOur ex vivo culture process supports scalable ProT-NK cell production in high yields, reducing dependency on feeder cells and mitigating contamination risks. Our findings demonstrate the feasibility of generating large, functional NK cell populations from HSPCs isolated from readily available cord blood sources and offer an efficient alternative to PB-NK cell therapies.